(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2009)
Incidence, population fluctuations and damage severity of pod borer, Helicoverpa armigera (Hubner) chickpea was studied at Regional Agricultural Research Station, Ishurdi, Pabna, Bangladesh during rabi crop seasons of 2003-04 and 2004-05. The incidence started in 2nd to 4th week of January irrespective of sowing dates. The borer population fluctuated depending on the dates of sowing. Pod borer population was higher in the early sown crops (October 15 to November 01) and with delayed the dates of sowing from November 01 to 30 population was decreased and then increased again. It was observed that both the early (October 15 to November 01) and late sown (December and onward) crops received higher pod borer damage and produced lower yield. But mid sown (November 08 to 30) crops received less pod borer damage and produced higher yield. Hence, for ensuring higher yield with less pod borer damage, chickpea should be sown within the range of November 08 to 30 and the best date of sowing seems to be November 15. Key words: Chickpea, Pod borer, Population fluctuation, Damage severity, Yield. DOI: 10.3329/bjsir.v44i2.3676 Bangladesh J. Sci. Ind. Res. 44(2), 221-224, 2009